Transcriptomics reveals a distinct metabolic profile in T cells from severe allergic asthmatic patients - Pablo-Torres, Carmela; Garcia-Escribano, Carlota; Romeo, Martina; Gomez-Casado, Cristina; Arroyo Solera, Ricardo; Bueno-Cabrera, José Luis; del Mar Reaño Martos, M.; Iglesias-Cadarso, Alfredo; Tarín, Carlos; Agache, Ioana; Chivato, Tomás; Barber, Domingo; et al. (Frontiers in Allergy, 2023)
Mechanisms causing the onset and perpetuation of chronic inflammation in severe allergic patients remain unknown. Previous results suggested that severe allergic inflammation is linked to systemic metabolic alterations and impairment of regulatory functions. Here, we aimed to identify transcriptomic alterations in T cells associated with the degree of severity in allergic patients. T cells were isolated from severe (n=7) and mild (n=9) allergic asthmatic patients, and control (non-allergic, healthy) subjects (n=7) to perform RNA analysis by Affymetrix gene expression. Significant transcripts were used to identify compromised biological pathways in the severe phenotype. T cells’ transcriptome of severe allergic patients was distinct from that of mild and non-allergic subjects. The severe allergic group showed a greater number of differentially expressed genes (DEGs) vs control (4924 genes) and vs mild (4232 genes) groups. Mild group also had 1102 DEGs vs controls. Pathway analysis revealed alterations in metabolism and immune response in the severe phenotype. Severe allergic patients presented downregulation in genes related to oxidative phosphorylation, fatty acid oxidation and glycolysis together with increased expression of genes coding inflammatory cytokines (e.g. IL-19, IL-23A and IL-31). Moreover, the downregulation of genes involved in TGFβ pathway together with a decreased number of T regulatory cells (CD4+CD25+), suggest a compromised regulatory function in severe allergic patients. This study demonstrates a downregulation of metabolic and cell signalling pathways in T cells of severe allergic asthmatic patients associated with diminished regulatory T cell function. These findings support a link between energy metabolism of T cells and allergic inflammation.